Portuguese version of the Short-Form Condom Attitude Scale and psychometric properties among undergraduate students - Zucoloto, Miriane Lucindo; da Silva, Wanderson Roberto [UNESP]; Silva, Rafaella Alves; Prudencio, Jonathan Leonardo Gonçalves; Frazatto, Vitoria de Souza Pinto; Martinez, Edson Zangiacomi (FapUNIFESP (SciELO), 2024)
The condom use can be influenced by psychological and sociocultural aspects, which can be modulated by individual’s attitudes. The aim was to propose a Brazilian Portuguese version of the Short-Form Condom Attitude Scale (Short-Form CAS), describing all procedures of translation, transcultural adaptation, and psychometric properties evaluation when applied to undergraduate students. A cross sectional study was conducted among students enrolled at University of São Paulo (USP), Campus Ribeirão Preto (n = 491; 61.2% female; average age: 22 years; standard deviation: four years). Confirmatory factor analysis was performed. A one-factor model with seven items exhibited good factorial validity and reliability, suggesting to be a better factorial solution of the Short-Form CAS in the sample. Few studies have been carried out on the behavioral factors associated with condom use in key populations, which can be exacerbated by a lack of appropriate scales. Therefore, the main contribution of the present study was to propose a simplified and transculturally adapted version of the Shortform CAS with some psychometric properties verified. Since the use of condoms is a component of the study of sexual risk behavior, this scale might be an option to be applied in various Brazilian population segments for this purpose.
Versão em português da Short-Form Condom Attitude Scale e propriedades psicométricas entre estudantes universitários
Keywords: Condom; Reliability; Sexual behaviors; Validation study; Youth